Respectful Maternity Care in South Asia: What Does the Evidence Say? Experiences of Care and Neglect, Associated Vulnerabilities and Social Complexities - Kaphle S; Vaughan G; Subedi M (Dove Medical Press, 2022)
Sabitra Kaphle,1 Geraldine Vaughan,2 Madhusudan Subedi3 1Central Queensland University, School of Health, Medical and Applied Sciences, Melbourne, VIC, 3000, Australia; 2Central Queensland University, School of Health, Medical and Applied Sciences, Sydney, NSW, 2000, Australia; 3School of Public Health, Patan Academy of Health Sciences, Kathmandu, NepalCorrespondence: Sabitra Kaphle, Central Queensland University, School of Health, Medical and Applied Sciences, Melbourne, VIC, 3000, Australia, Email s.kaphle@cqu.edu.auBackground: Respectful maternity care encompasses the right to continuity of care and dignified support for women during the reproductive period, enabling informed choice. However, the evidence is limited in the context of South Asia region where maternal, perinatal and newborn mortality is still a critical challenge to health systems. Evidence is required to better understand the context of respectful maternity care to inform directions for appropriate policy and practice.Objective: The objective of this scoping review was to explore facilitators and barriers of respectful maternity care practice in South Asia.Design: CINAHL, EMBASE, PubMed, Medline, SCOPUS and Cochrane databases were used to identify related studies. Data were systematically synthesized and analysed thematically.Findings: There was considerable heterogeneity in the 61 included studies from seven South Asian countries, with most of the research conducted in Nepal and India. While the experience of abuse and neglect was common, 10 critical themes emerged related to neglected choices and compromised quality of care (particularly where there were health inequities) in the context of institutional care experiences; and the imperative for improved investment in training and significant policy and legislative change to enforce equitable and respectful maternity care practice.Conclusions and Implications for Practice: Evidence about respectful maternity care in South Asia indicates that women accessing professional and facility-based services experienced high levels of disrespect, abuse and maltreatment. Women from vulnerable, socially disadvantaged and economically poor backgrounds were more likely to experience higher level abuse and receive poor quality of care. There is an urgent need for a well-resourced, sustained commitment to mandate and support the provision of respectful and equitable maternity care practice in South Asia.Keywords: maternal health, respect, pregnancy, maternity care, health service, South Asia